Procedure to Improve Risk Identification Inbasement Excavation Using BIM and GIS in Multifamily Housing Projects - Baltodano, Junior Bardales (2025)
This study proposes a comprehensive guide to improve safety planning in basement excavation projects through the integration of BIM (Building Information Modeling) and GIS (Geographic Information Systems). The guide focuses on training personnel and applying these tools in selected projects, addressing deficiencies in safety planning in Peru. The methodology includes the creation of three-dimensional models and geospatial analysis to anticipate and mitigate risks, optimizing data management and risk visualization. The implementation of BIM and GIS in a multi-family project in Lima showed a significant improvement in safety, reducing incidents from 9 to 1 in basement 4 compared to basement 3. Personnel training increased from 85% to 100%, and safety perception improved, with a reduction from 25% to 8% in reported risk conditions. The guide also reduced minor incidents during excavations by 20%. Validation of the methodology demonstrated an average reduction of three days in response to potential risks, highlighting the effectiveness of BIM and GIS in safety planning. Personnel satisfaction with the guide reached 85%, compared to 40% with traditional methods, emphasizing its utility in enhancing safety and efficiency in basement excavation.